Partitioning of radiological, stress and biochemical changes in pre-diabetic women subjected to Diabetic Yoga Protocol. Issue 4 (July 2019) - Singh, Amit Kumar; Kaur, Navneet; Kaushal, Sushant; Tyagi, Rahul; Mathur, Deepali; Sivapuram, Madhava Sai; Metri, Kashinath; Bammidi, Sridhar; Podder, Vivek; Modgil, Shweta; Khosla, Radhika; Sharma, Kiran; et al.
Abstract: Background: Yoga is an ancient system of wellness with Asana and Pranayama as its most popular and propagated modules for management of lifestyle disorders. Objectives: The aim of the study was to characterise the liver abnormalities, biochemical changes, and stress levels after Yoga intervention in prediabetic females. Materials and methods: 37 females were randomly divided into Yoga practising and non-practising control groups. The Yoga practising group performed Diabetic Yoga Protocol (DYP) for 3 months. Parameters including size of liver, fatty infiltration, and grade of severity were measured using ultrasonography along with biochemical parameters and stress levels at baseline and after Yoga practice. Results: The glycosylated hemoglobin (HbA1c) and glucose levels were found significantly reduced in prediabetic (p = 0.015) women after practising DYP, although cholesterol levels increased in menopausal women. No escalation of fatty liver was noted among women practising DYP. Conclusion: DYP reduced the HbA1c and stress levels and therefore, could be a cost-effective tool for preventing prediabetes to diabetes progression.